Visualizing a political actor in Pacific War: The role of Manuel Velarde in the governments of Francisco García Calderón and Lizardo Montero (1881-1883) - Abanto Chani, Julio (2021)
Manuel Velarde was an important man, politician, and military who had a relevant role during the War of the Pacific (1879-1884). Thanks to the unpublished information provided by various documentary collections, his political participation is reconstructed after the fall of Lima (January 1881), especially during the governments of Francisco García Calderón (where he was Minister of Government) and Lizardo Montero (as Chief of the South Army, Minister of War, and Chairman of the Council of Ministers), which had not been analyzed in greater depth by the Peruvian historiography. Likewise, the character of Velarde as a political articulator and operator is notorious for alternating his functions as a government official with the strengthening of relations with other figures in the high political spheres related to civilism (Camilo Carrillo in Arequipa, Francisco García Calderón in Chile and Manuel María del Valle in La Paz) and the alliance with Bolivia and General Campero.